Competition of infectious hypodermal and haematopoietic necrosis virus (IHHNV) with white spot syndrome virus (WSSV) for binding to shrimp cellular membrane. Issue 10 (12th May 2016) - Yan, D C; Huang, J; Yang, B; Sun, H S; Wang, Y Y; Liu, X
Abstract: Infectious hypodermal and haematopoietic necrosis virus (IHHNV) and white spot syndrome virus (WSSV) are two widespread shrimp viruses. The interference of IHHNV on WSSV was the first reported case of viral interference that involved crustacean viruses and has been subsequently confirmed. However, the mechanisms underlying the induction of WSSV resistance through IHHNV infection are practically unknown. In this study, the interference mechanisms between IHHNV and WSSV were studied using a competitive ELISA. The binding of WSSV and IHHNV to cellular membrane of Litopenaeus vannamei was examined. The results suggested that there existed a mutual competition between IHHNV and WSSV for binding to receptors present on cellular membrane of L. vannamei and that the inhibitory effects of WSSV towards IHHNV were more distinct than those of IHHNV towards WSSV.